LAMINATE AND METHOD FOR MANUFACTURING LAMINATE

The laminate, featuring a specific polyethylene resin composition and an adhesive layer with polyol and polyisocyanate reactants, addresses the challenges of poor tearability and adhesion in existing laminates, resulting in improved handling and protection of packaged contents.

JP7669905B2Active Publication Date: 2025-04-30JAPAN POLYETHYLENE CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021179033
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-04-30
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

Existing laminates used in packaging face challenges with poor tearability, requiring force to open, and issues with straw penetration in liquid paper containers, due to inadequate adhesion and handling properties.

Method used

A laminate structure comprising at least four layers: a substrate layer, a resin layer with a specific polyethylene resin composition containing an ethylene copolymer with defined properties, an adhesive layer containing a reactant of a polyol compound and a polyisocyanate compound, and another substrate layer, which enhances adhesion, tearability, and handling characteristics.

Benefits of technology

The laminate achieves excellent adhesion to substrates, improved tearability, and enhanced handling properties, allowing for easy opening and effective protection of contents, while also improving high-speed processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669905000001
    Figure 0007669905000001
Patent Text Reader

Abstract

To provide a laminate which is excellent in both good adhesion to a base material, and easy-to-open handleability such as good easy tearability, and a method for manufacturing a laminate.SOLUTION: A laminate has at least four layers of a base material layer 1 (A), a resin layer (B), an adhesive layer (C), and a base material layer 2 (D), wherein the base material layer 1 (A), the resin layer (B), the adhesive layer (C), and the base material layer 2 (D) are mutually adjacently laminated, and the resin layer (B) and the adhesive layer (C) satisfy the following characteristics. Resin layer (B): containing a polyethylene resin composition (B) containing an ethylene-based copolymer (A) having characteristics (a-1) to (a-4). Adhesive layer (C): containing a reactant of a polyol compound and a polyisocyanate compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a method for producing the laminate, and more particularly to a laminate including a first base material layer, a resin layer containing a polyethylene resin composition made of a specific ethylene-based copolymer or the like, an adhesive layer containing a reaction product of a specific compound, and a second base material layer, and a method for producing the laminate. [Background technology]

[0002] Conventionally, in order to improve the storage stability of the contents of packages, containers, etc., laminates have been used that are made of metal foils such as aluminum with barrier properties, plastic films onto which metals, inorganic substances, or organic substances have been vapor-deposited, plastic films or paper base materials with barrier coatings, films of barrier materials such as ethylene-vinyl alcohol copolymers, or laminated films made of the same or different materials. In these laminates, polyethylene resin compositions consisting of high-pressure low-density polyethylene (LDPE), ethylene-vinyl acetate copolymer (EVA), etc. have been used as heat seal layers. In recent years, linear low-density polyethylene (LLDPE), especially LLDPE polymerized with a metallocene catalyst, has been proposed for use as a sealant for soft packaging, liquid paper containers, etc., in order to improve the heat seal strength, low-temperature heat sealability, hot tackiness, impact resistance, pinhole resistance, etc. of these laminates, and it has been widely used as a sealant for soft packaging, liquid paper containers, etc. However, in easy-tear packaging applications, it has problems such as requiring force to open due to poor tearability and stretching of the resin layer. In addition, for containers with straw holes such as liquid paper containers, it has problems such as poor penetration of the straw.

[0003] These laminates are manufactured by dry lamination, coextrusion molding, and extrusion lamination molding. In extrusion lamination molding, an adhesive may or may not be applied, and in either case, a stable high adhesive strength is required. Many attempts have been made to solve these problems. For example, a laminate of LLDPE polymerized with a metallocene catalyst and LLDPE polymerized with a Ziegler catalyst has been proposed (see Patent Document 1). However, although the tearability of this laminate is somewhat improved by the LLDPE polymerized with a Ziegler catalyst, the elongation of the LLDPE layer polymerized with a metallocene catalyst cannot be eliminated, and above all, heat sealability is significantly sacrificed, making this method undesirable. Furthermore, there is no description regarding adhesion to substrates. Furthermore, an invention has been proposed in which LDPE having a specific swell ratio is blended with LLDPE polymerized with a metallocene catalyst (see Patent Document 2), but the balance between heat seal strength and tear resistance is not satisfactory, and Patent Document 2 is silent about adhesion to substrates. In addition, Patent Document 3 by the present applicant also discloses an invention in which an ethylene terpolymer essentially consisting of ethylene, propylene, and 1-hexene or 1-octene is blended with LDPE (see Patent Document 3), but there is no description regarding pierceability and adhesiveness. As a method that does not use an adhesive, a method that uses a polyethylene resin that exhibits specific physical properties or contains a specific copolymer (see Patent Document 4) has been proposed. However, Patent Document 4 does not include any description regarding adhesive strength and tearability, and there is no disclosure of a method that has excellent adhesive strength and tearability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-24539 [Patent Document 2] JP 2000-212339 A [Patent Document 3] JP 2006-82547 A [Patent Document 4] JP 2001-191452 A Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above problems, an object of the present invention is to provide a laminate excellent in both adhesion to a substrate and ease of opening and handling, such as ease of tearing, and a method for producing the laminate. [Means for solving the problem]

[0006] As a result of intensive research to solve the above problems, the present inventors have newly discovered that an ethylene-based copolymer having the physical properties (a-1) to (a-4) shown below, i.e., an ethylene-based copolymer having MFR, total heat of fusion, and crystallization temperature in certain ranges, and a resin layer using a polyethylene resin composition containing an ethylene-based copolymer containing a main component which is ethylene and a predetermined amount of a subcomponent other than ethylene, and an adhesive layer containing a reaction product of a polyol compound and a polyisocyanate compound, has excellent adhesion and excellent tearability, and is a laminate having excellent content protection performance and handleability while balancing both performances, thereby completing the present invention.

[0007] That is, the first invention of the present invention has at least four layers: a base layer 1 (a), a resin layer (b), an adhesive layer (c), and a base layer 2 (d), The laminate is characterized in that a base layer 1 (a), a resin layer (b), an adhesive layer (c), and a base layer 2 (d) are laminated adjacent to each other, and the resin layer (b) and the adhesive layer (c) each satisfy the following properties: Resin layer (ii): Contains a polyethylene resin composition (B) that contains an ethylene copolymer (A) having the following characteristics (a-1) to (a-4). (a-1) MFR (190°C, 21.18N load) is 0.1 to 100g / 10min (a-2) In DSC, the total heat of fusion ΔHm is 30 to 120 J / g (a-3) Crystallization temperature Tc is 25 to 90°C (a-4) Contains 70 to 98 mol % of structural units derived from ethylene as a major component, and 2 to 30 mol % of structural units other than ethylene as essential minor components. Adhesive layer (C): Contains a reaction product of a polyol compound and a polyisocyanate compound.

[0008] In addition, the second aspect of the present invention is a polyethylene resin composition (B) comprising the following (c-1 The laminate according to the first aspect of the present invention is characterized in that it contains a polyethylene resin (C) having the characteristics (c-1) to (c-2). (c-1) MFR (190℃, 21.18N load) is 0.1 to 100g / 10min (c-2) Density is 0.91 to 0.97 g / cm 3

[0009] The third invention of the present invention provides the laminate according to the second invention, characterized in that a content ratio (weight ratio A:C) of the ethylene copolymer (A) to the polyethylene resin (C) in the polyethylene resin composition (B) is 98-2:2-98.

[0010] A fourth aspect of the present invention provides the laminate according to any one of the first to third aspects, wherein the polyethylene resin composition (B) further satisfies the following properties (b-1) to (b-2): (b-1) MFR (190°C, 21.18N load) is 1 to 100g / 10min (b-2) Density is 0.88 to 0.94 g / cm 3

[0011] A fifth aspect of the present invention provides the laminate according to any one of the first to fourth aspects, wherein the ethylene-based copolymer (A) further satisfies the following properties (a-5) to (a-7): (a-5) Contains 80 to 98 mol% of structural units derived from ethylene as a major component, 2 to 20 mol% of structural units derived from propylene as an essential minor component, and may contain 5 mol% or less of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the structural units derived from the third α-olefin are contained, the total content of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (a-6) Density is 0.88 to 0.94 g / cm 3 (a-7) The total amount of vinyl and vinylidene in the ethylene copolymer is 0.35 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene units is the number per 1,000 carbon atoms in the main chain and side chains, measured by NMR.)

[0012] A sixth aspect of the present invention provides the laminate according to any one of the first to fifth aspects, wherein the ethylene-based copolymer (A) further satisfies the following characteristic (a-8): (a-8) The number of branches (Y) due to comonomers in the ethylene copolymer and the density (X) satisfy the relationship of the following formula (1). Formula (1): (Y) ≧ -1157×(X)+1080 (where Y is the number per 1000 carbon atoms in total in the main chain and side chains as measured by NMR.)

[0013] A seventh aspect of the present invention provides the laminate according to any one of the first to sixth aspects, wherein the ethylene-based copolymer (A) further satisfies the following characteristic (a-9): (a-9) The number of branches (Y) due to comonomers in the ethylene copolymer and the density (X) satisfy the relationship of the following formula (2). Formula (2): (Y) ≧ -1157×(X)+1084 (where Y is the number per 1000 carbon atoms in total in the main chain and side chains as measured by NMR.)

[0014] The eighth aspect of the present invention is a method for manufacturing a refractory material having an oxygen permeability of 1300 mL / m under conditions of 20° C. and 65% RH. 2 The laminate according to any one of the first to seventh aspects of the present invention is characterized in that the compressive strength is 0.05 MPa or less.

[0015] A ninth aspect of the present invention provides the laminate according to any one of the first to eighth aspects, characterized in that the laminate is formed by extrusion coating.

[0016] The tenth aspect of the present invention provides a method for producing the laminate according to any one of the first to ninth aspects of the present invention. Effect of the Invention

[0017] The laminate and the method for producing the laminate of the present invention exhibit good adhesion to the substrate and easy tearability, and are excellent in protecting the contents and in handling when opened. In addition, the high-speed processability of the laminate can be improved with the improved adhesive strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention relates to a laminate having at least four layers, namely, a base layer 1 (a), a resin layer (b), an adhesive layer (c), and a base layer 2 (d), in which the base layer 1 (a), the resin layer (b), the adhesive layer (c), and the base layer 2 (d) are laminated adjacent to one another, and the laminate contains a resin layer (b) containing a polyethylene resin composition (B) containing an ethylene-based copolymer (A) having the following characteristics (a-1) to (a-4) and, if necessary, further (a-5) to (a-9) and a polyethylene resin (C) having the following characteristics (c-1) to (c-2), and an adhesive layer (c) containing a specific compound. The present invention will be described in detail below for each item.

[0019] 1. Polyethylene resin composition (B) (1) Ethylene-based copolymer (A) The ethylene copolymer (A) used in the present invention has the following properties (a-1) to (a-4): The present invention is characterized by satisfying all of the above requirements and, if necessary, further satisfying the requirements (a-5) to (a-9).

[0020] (a-1) Melt flow rate (MFR) The melt flow rate (MFR: 190°C, 21.18N load) of the ethylene copolymer (A) used in the present invention is 0.1 to 100g / 10min, preferably 1 to 80g / 10min, more preferably 5 to 70g / 10min. If the MFR is less than 0.1g / 10min, the extensibility during molding is poor and the motor load in the extruder is high, which is not preferable. On the other hand, if the MFR exceeds 100g / 10min, the state of the molten film during molding becomes unstable, which is not preferable. To adjust the MFR of the ethylene copolymer, for example, there is a method of appropriately adjusting the polymerization temperature, the amount of comonomer, etc. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Appendix (190°C, 21.18N load).

[0021] (a-2) Total heat of fusion ΔHm The total heat of fusion ΔHm of the ethylene copolymer (A) used in the present invention is 30 to 120 J / g, preferably 32 to 118 J / g, and more preferably 35 to 115 J / g. If ΔHm is less than 30 J / g, blocking becomes poor, which is not preferable. On the other hand, if ΔHm exceeds 120 J / g, the adhesiveness becomes poor, which is undesirable. In order to adjust ΔHm of the ethylene copolymer, for example, a method of appropriately adjusting the comonomer content, polymerization temperature, catalyst amount, etc. can be used. Here, ΔHm indicates the heat of fusion in the melting curve measured by a differential scanning calorimeter (DSC). In general, ethylene resins with low crystallinity tend to have a broader melting peak and a smaller ΔHm than ethylene resins with high crystallinity.

[0022] (a-3) Crystallization temperature Tc The crystallization temperature Tc of the ethylene copolymer (A) used in the present invention is 25 to 90° C., preferably 27 to 88° C., and more preferably 30 to 85° C. If Tc is less than 25° C., the crystallinity is too low, which is undesirable as blocking is poor. On the other hand, if Tc is more than 90° C., the adhesiveness is undesirable as a result of the presence of highly crystalline components. Here, Tc indicates the maximum peak temperature among the crystallization peaks in the crystallization curve measured by a differential scanning calorimeter (DSC).

[0023] (a-4) Monomer structure of ethylene copolymer (A) The ethylene-based copolymer (A) used in the present invention is an ethylene-based copolymer characterized by containing 70 to 98 mol% of structural units derived from ethylene as a main component and 2 to 30 mol% of structural units derived from comonomers other than ethylene as a secondary component. Preferably, the structural units derived from ethylene are 72 to 97 mol%, the structural units derived from comonomers other than ethylene are 3 to 28 mol%, more preferably, the structural units derived from ethylene are 75 to 95 mol%, and the structural units derived from propylene are 5 to 25 mol%. If the structural units derived from ethylene are less than 70 mol%, blocking becomes poor, which is not preferable. On the other hand, if the structural units derived from ethylene are more than 98 mol%, adhesion becomes poor, which is not preferable. Here, the monomer amount such as the ethylene content is 13 The values ​​were measured and calculated by C-NMR under the conditions described in the Examples section below. The type of comonomer may be one or a combination of two or more types as long as it satisfies (a-1) to (a-4), more preferably (a-5) to (a-9). The ethylene copolymer (A) may be one or a combination of two or more types as long as it satisfies (a-1) to (a-4), more preferably (a-5) to (a-9). Specific examples of the comonomer include α-olefins such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-heptene, 4-methyl-pentene-1, 4-methyl-hexene-1, and 4,4-dimethylpentene-1; diene compounds such as 1,5-hexadiene, 1,6-heptadiene, 1,7-octadiene, 1,8-nonadiene, and 1,9-decadiene; and acids and ester compounds such as vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, maleic anhydride, methacrylic acid, and metal ion-containing methacrylic acid. The comonomers may be of one type or a combination of two or more types.

[0024] (a-5) Propylene-derived minor components The ethylene-based copolymer (A) used in the present invention is an ethylene-based copolymer characterized by containing 80 to 98 mol% of structural units derived from ethylene as a main component and 2 to 20 mol% of structural units derived from propylene as a secondary component, and specifically, a copolymer polymerized by catalytic polymerization method, which is a copolymer polymerized substantially randomly in a linear chain. A specific example is a random copolymer of ethylene and propylene. Preferably, the structural units derived from ethylene are 82 to 97 mol%, the structural units derived from propylene are 3 to 18 mol%, and more preferably, the structural units derived from ethylene are 85 to 95 mol%, and the structural units derived from propylene are 5 to 15 mol%. Here, the monomer amount such as the ethylene content is 13 The values ​​were measured and calculated by C-NMR under the conditions described in the Examples below.

[0025] In addition, it is preferable that the copolymer does not contain any other α-olefins, particularly α-olefins having 4 to 20 carbon atoms, or other monomer components, but may contain such components in a substantially small amount. In this specification, an α-olefin other than ethylene and propylene is referred to as a third α-olefin. The ethylene-based copolymer (A) of the present invention may contain, as a secondary component, a structural unit derived from a third α-olefin other than ethylene and propylene, for example, in an amount of 5 mol% or less, preferably 2 mol% or less, more preferably 1.5 mol% or less, even more preferably 1 mol% or less, and most preferably 0.5 mol% or less. Here, when the ethylene-based copolymer (A) of the present invention contains a structural unit derived from a third α-olefin, the total amount of the structural unit derived from ethylene, the structural unit derived from propylene, and the structural unit derived from the third α-olefin does not exceed 100 mol%. In this case, the content of the structural unit derived from propylene is preferably higher than the content of the structural unit derived from the third α-olefin. When the ethylene copolymer (A) of the present invention contains a structural unit derived from a third α-olefin, one or more kinds of the third α-olefin can be used.

[0026] When propylene is used as a secondary component and is an essential comonomer, and in particular when high-pressure ionic polymerization using a metallocene catalyst (described later) is employed, it is possible to obtain ethylene-α-olefin copolymers with a specifically high total number of vinyl and vinylidene units. On the other hand, when α-olefins such as 1-hexene and 1-octene are polymerized as the main comonomer, this effect is difficult to obtain.

[0027] In addition, copolymers consisting of ethylene and propylene include so-called ethylene propylene rubber (EPM), which contains more than 20 mol% propylene and has a density of 0.870 g / cm 3 Rubber-like polymers obtained by the following solution polymerization method are used in the field of elastomers, but the ethylene-based copolymer (A) of the present invention is a polymer that is completely different from these ethylene-propylene rubbers in terms of density range, amount of ethylene and propylene contained therein, and physical properties. In addition, among propylene polymers, propylene-ethylene copolymers that contain a small amount of ethylene component during the production process are also known, but these are also polymers that are significantly different from the ethylene copolymer (A) of the present invention in terms of propylene content, etc., and are also completely different in physical properties, etc.

[0028] (a-6) Density The ethylene copolymer (A) used in the present invention has a density of 0.88 to 0.94 g / cm 3 and preferably 0.885 to 0.94 g / cm 3 and more preferably 0.89 to 0.93 g / cm 3 The density is 0.88g / cm 3 If the density is less than 0.94 g / cm3, blocking will be poor, which is not preferable. 3 If it exceeds this value, the adhesiveness will be poor, which is not preferable. The density of the polymer can be adjusted by, for example, appropriately adjusting the comonomer content, polymerization temperature, catalyst amount, etc. The density of the ethylene copolymer is measured in accordance with JIS-K6922-2:1997 Appendix (for low density polyethylene) (measurement temperature 23°C).

[0029] (a-7) Total amount of vinyl and vinylidene In copolymers obtained by copolymerizing ethylene with one or more α-olefins, even if diene monomers are not actively added, various double bonds (vinyl, vinylidene, cis-vinylene, trans-vinylene, tri-substituted olefins) may be produced due to differences in the mechanisms of the manufacturing process, and the amounts and types of double bonds vary. It has been known that in order to obtain good cross-linking properties for use as a solar cell encapsulant, the more double bonds contained in an ethylene-α-olefin copolymer, the better the cross-linking properties. However, in the field of laminates using polyethylene resin compositions, which require good adhesion, the differences resulting from the amount and type of double bonds had not been investigated. In the present invention, it has been found that, among various double bonds contained in an ethylene-based copolymer, vinyl and vinylidene are particularly important in terms of achieving both adhesive strength and easy tearability, and it has also been found that the effects of the present invention can be achieved by producing an ethylene-based copolymer in which the total amount of vinyl and vinylidene is greater than that of a copolymer usually obtained, and using the ethylene-based copolymer for a polyethylene resin composition for laminates, and the invention has been completed based on this discovery.

[0030] The ethylene-based copolymer (A) used in the present invention has a total amount of vinyl and vinylidene double bonds per total of 1000 carbon atoms in the main chain and side chains as measured by NMR of 0.35 (units / total 1000C) or more, preferably 0.40 to 5.0 (units / total 1000C), and more preferably 0.45 to 4.5 (units / total 1000C); More preferably, it is 0.50 to 4.0 (pieces / total 1000C). When the total amount of vinyl and vinylidene is within the above range, the laminate resin composition has excellent adhesive strength, and when it is less than 0.35, the adhesive strength is insufficient. The total amount of vinyl and vinylidene can be controlled within the above range by appropriately selecting a suitable metallocene catalyst, adjusting the polymerization temperature, and the type of comonomer. The number of vinyl and vinylidene can be adjusted by the production conditions such as the type of comonomer, the amount of comonomer, and the polymerization temperature. The number of double bonds is per 1,000 carbon atoms in the main chain and side chains combined. 1 This value was calculated using the integrated intensity of a characteristic peak in the H-NMR spectrum, and was measured and calculated under the conditions described in the Examples section below.

[0031] Furthermore, in the present invention, the number of vinyl groups in the ethylene copolymer (A) preferably satisfies the range of 0.2 (groups / total 1000C) or more. In the present invention, the number of vinylidene units in the ethylene copolymer (A) preferably satisfies the range of 0.12 (units / total 1000C) or more.

[0032] (a-8) Relationship between branch number (Y) and density (X) due to comonomer The ethylene copolymer (A) used in the present invention preferably satisfies the requirements for the number of branches (Y) due to the comonomer and the density (X). Formula (1): (Y) ≧ -1157×(X)+1080 When the density and the number of branches are within the above ranges, the polyethylene resin composition has excellent tearability and adhesive strength.

[0033] The number of branches (Y) due to comonomers indicates the amount of tertiary carbons contained in the polymer, and is the number per 1000 carbons in total in the main chain and side chains, as measured by NMR. For example, see EW Hansen, R. Blom, and OM Bade, Polymer, Vol. 36, p. 4295 (1997). 13 It can be calculated from the C-NMR spectrum. The relationship between the density and the number of branches can be adjusted by the polymerization conditions such as the type and ratio of the comonomers to be copolymerized and the polymerization temperature.

[0034] (a-9) Relationship between branch number (Y) and density (X) due to comonomer The ethylene copolymer (A) used in the present invention preferably satisfies the requirements for the number of branches (Y) due to the comonomer and the density (X). Formula (2): (Y) ≧ -1157×(X)+1084 When the density and the number of branches are within the above ranges, the polyethylene resin composition has excellent tearability and adhesive strength. The relationship between the density and the number of branches can be adjusted by the type and ratio of the comonomers to be copolymerized.

[0035] <Polymerization method for ethylene copolymer (A)> The method for producing the ethylene copolymer (A) used in the present invention that satisfies (a-1) to (a-4) is not particularly limited, and a high-pressure radical polymerization method, a high-pressure ionic polymerization method, a gas phase method, a solution method, a slurry method, etc. can be used.

[0036] More preferably, the catalyst used in the production of the ethylene copolymer (A) satisfying (a-5) to (a-9) is not particularly limited, but more preferably, a metallocene catalyst is used. The metallocene catalyst is not particularly limited, but may be a catalyst containing a metallocene compound such as a zirconium compound coordinated with a group having a cyclopentadienyl skeleton and a cocatalyst as a catalyst component. In particular, it is preferable to use a metallocene compound such as a zirconium compound coordinated with a group having a cyclopentadienyl skeleton. The production method is not particularly limited, and a high-pressure ionic polymerization method, a gas phase method, a solution method, a slurry method, etc. can be used. However, in order to obtain the ethylene copolymer (A) according to the present invention in which the double bonds are adjusted, it is desirable to carry out the polymerization at a high temperature of 150 to 330°C, and therefore it is preferable to use a high-pressure ionic polymerization method (see Chapter 4 of "Polyethylene Technology Reader," edited by Kazuo Matsuura and Naotaka Mikami). Author, 2001).

[0037] (2) Polyethylene resin (C) The polyethylene resin (C) contained in the polyethylene resin composition (B) of the present invention is a polyethylene having the following characteristics (c-1) and (c-2), and is preferably a low-density polyethylene.

[0038] (c-1) Melt flow rate (MFR) The melt flow rate (MFR) of the polyethylene resin (C) used in the present invention is 0.1 to 100 g / 10 min, preferably 0.5 to 50 g / 10 min, and more preferably 1 to 20 g / 10 min. If the MFR is less than 0.1 g / 10 min, the extensibility is insufficient and film breakage occurs during high-speed molding. On the other hand, if the MFR exceeds 100 g / 10 min, the molten film becomes unstable. Here, the MFR is a value measured in accordance with JIS-K7210 (190°C, 21.18 N load).

[0039] (c-2) Density The density of the polyethylene resin (C) used in the present invention is 0.91 to 0.97 g / cm 3 and preferably 0.915 to 0.96 g / cm 3and more preferably 0.916 to 0.95 g / cm 3 The density is 0.91g / cm 3 If it is less than 0.97g / cm, it will be sticky. 3 If it exceeds this value, the adhesion becomes poor. Here, the density is measured (23° C.) in accordance with JIS-K6922-2:1997 Appendix (for low-density polyethylene).

[0040] The method for producing the polyethylene resin (C) used in the present invention is not particularly limited, and may be a high-pressure radical polymerization method, a high-pressure ionic polymerization method, a gas phase method, a solution method, a slurry method, etc. In addition, when producing low-density polyethylene, a tank type reactor or a tubular type reactor is generally used in the presence of a radical generator at a polymerization pressure of 1000 to 3000 kg / cm. 2 It is carried out by polymerizing ethylene at a polymerization temperature of 150 to 300°C. The MFR can be adjusted by using hydrogen or hydrocarbons such as methane and ethane as molecular weight regulators.

[0041] (3) Content ratio of ethylene copolymer (A) and polyethylene resin (C) In the polyethylene resin composition (B) used in the present invention, the content ratio (weight ratio) of the ethylene copolymer (A) to the polyethylene resin (C), (A):(C), is 98-2:2-98, preferably 90-2:10-98, more preferably 80-2:20-98, and further preferably 70-5:30-95. If the amount of the ethylene copolymer (A) is too large, the stability of the molten film is deteriorated. In particular, the ratio (weight ratio) of the ethylene copolymer (A) to the polyethylene resin (C) is preferably 50-5:50-95, more preferably 40-5:60-95, since this achieves a good balance between adhesive strength and molten film stability.

[0042] (4) Characteristics of polyethylene resin composition (B) (b-1) Melt flow rate (MFR) The melt flow rate (MFR: 190°C, 21.18N load) of the polyethylene resin composition (B) used in the present invention is 1 to 100g / 10min, preferably 1 to 80g / 10min, and more preferably 2 to 70g / 10min. If the MFR is less than 1g / 10min, the extensibility during molding is deteriorated and the motor load in the extruder is increased, which is not preferable. On the other hand, if the MFR exceeds 100g / 10min, the state of the molten film during molding becomes unstable, which is not preferable. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Appendix (190°C, 21.18N load).

[0043] (b-2) Density The density of the polyethylene resin composition (B) used in the present invention is 0.88 to 0.94 g / cm 3 and preferably 0.885 to 0.94 g / cm 3 and more preferably 0.89 to 0.935 g / cm 3 The density is 0.88g / cm 3 If the density is less than 0.94 g / cm3, blocking will be poor, which is not preferable. 3 If it exceeds this value, the adhesiveness will be poor, which is not preferable.

[0044] (5) Other compounds The polyethylene resin composition (B) used in the present invention or the resin layer (ii) containing the same may contain additives such as phenol-based or phosphorus-based antioxidants, stabilizers such as metal soaps, antiblocking agents, lubricants, dispersants, pigments such as organic or inorganic colorants, antifogging agents such as unsaturated fatty acid esters, antistatic agents, ultraviolet absorbers, light stabilizers, and nucleating agents, which are commonly used in polyethylene resins, as necessary. The amount of additives added is preferably 700 ppm or less, more preferably 400 ppm or less, even more preferably 200 ppm or less, and most preferably 100 ppm or less. If the amount of additives added is too large, the adhesion becomes poor, which is not preferable. In addition, other thermoplastic resins such as polyethylene resins such as LDPE, C4-LLDPE, HAO-LLDPE, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-acrylic acid ester copolymer (EEA, EMA, EMMA, etc.), high density polyethylene (HDPE), etc., adhesive resins such as ethylene-maleic anhydride copolymer, polypropylene resins, polystyrene resins, etc. may be blended into the resin layer (b) as long as the properties of the resin layer (b) are not impaired.

[0045] 2. Adhesive layer (C) The adhesive layer (III) used in the present invention can be obtained by directly laminating an adhesive containing a reaction product of a polyol compound and a polyisocyanate compound onto the base layer 2 (IV) by a known means such as coating or extrusion, and then curing the same. As such an adhesive, a two-component curing polyurethane resin adhesive is preferable. By using an adhesive containing a reaction product of a polyol compound and a polyisocyanate compound as the adhesive layer (III), both adhesion and easy tearability can be achieved. The resulting adhesive layer (iii) contains a reaction product of a polyol compound and a polyisocyanate compound, and an adhesive that has been conventionally used in the extrusion coating method or the dry lamination method can be used. The polyol is a polyol component having at least two or more hydroxyl groups in the molecule. Examples of such polyol components include polyurethane polyol, polyester polyol, polyether polyol, acrylic polyol, and laminate resin composition polyol, and such polyol components can be used alone or in combination of two or more.

[0046] Examples of the isocyanate component having at least two isocyanate groups in the molecule include aromatic aliphatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates. Specific examples of aromatic aliphatic diisocyanates include 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof, and ω,ω'-diisocyanato-1,4-diethylbenzene. Specific examples of aliphatic diisocyanates include hexamethylene diisocyanate, tetramethylene diisocyanate, 2-methyl-pentane-1,5-diisocyanate, 3-methyl-pentane-1,5-diisocyanate, lysine diisocyanate, and trioxyethylene diisocyanate. Specific examples of alicyclic diisocyanates include isophorone diisocyanate, cyclohexyl diisocyanate, hydrogenated diphenylmethane diisocyanate, norbornane diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylene diisocyanate, hydrogenated tetramethylxylene diisocyanate, etc. It is possible to use one or more of such isocyanate components in combination.

[0047] Specifically, adhesives (anchor coat agents) used in extrusion lamination processing, A-3210 / A-3070, A-3210 / A3072, A-3210 / A-3075 (manufactured by Mitsui Chemicals, Inc.), Seikadyne 2710A / Seikadyne 2810C(T), Seikadyne 2730A / Seikadyne 2730B, Seikadyne 2710A / Seikadyne 2710C (manufactured by Dainichi Seika Chemicals Co., Ltd.), EL-510 / CAT-RT80, EL-530A / EL-530B, EL-540 / CAT-RT32 (manufactured by Toyo Morton Co., Ltd.), T-120A / T-300 hardener, T- Adhesives used in dry lamination include DIC Dry LX-401A, 75A, 719, 703VL, 500, 510 (manufactured by DIC Graphics), Takelac / Takenate A-909 / A-5, A-977 / A-92, A-606 / A-50, A-515 / A-50, A-626 / A-50, A-525 / A-52, A-666 / A-65 (manufactured by Mitsui Chemicals), RU-77, 771, 3600, 3900 (manufactured by Rock Paint), etc. In particular, it is preferable to use A-3210 / A-3070, A-3210 / A3072, A-3210 / A-3075 (manufactured by Mitsui Chemicals, Inc.), Seikadyne 2710A / Seikadyne 2810C(T), Seikadyne 2710A / Seikadyne 2710C (manufactured by Dainichi Seika Color & Chemicals Mfg. Co., Ltd.), EL-510 / CAT-RT80, EL-540 / CAT-RT32 (manufactured by Toyo-Morton Co., Ltd.), etc.

[0048] 3. Base layer 1 (a), base layer 2 (d) Examples of the substrate layer 1(a) and substrate layer 2(d) used in the present invention include monolayer films or sheets of polyamide, polyester, polypropylene, polyethylene, ethylene-vinyl alcohol copolymer, polyvinylidene chloride, polycarbonate, etc., laminated films or laminated sheets made of the same or different materials, stretched products of the above films or sheets, paper such as kraft paper, metal foils or metal plates such as aluminum, iron, copper, and alloys mainly made of these, plastic films or sheets vapor-deposited with metals, inorganic substances, or organic substances, cellophane, woven fabric, nonwoven fabric, paper or plastic film with a barrier coating, etc. The substrate layer 1(a) and substrate layer 2(d) may be of the same type or of different types. Among the above, from the viewpoint of protecting the contents, metal foils or metal plates of aluminum, iron, copper, alloys containing these as main components, etc., plastic films or sheets vapor-deposited with metals, inorganic substances, or organic substances, and paper or plastic films with a barrier coating are preferred as the base material layer 1(i).

[0049] The base layer 1(a) used in the present invention has an oxygen permeability of 1300 mL / m under conditions of 20° C. and 65% RH. 2 ·day·MPa or less is preferable. 2 It is more preferable that the base material has a compressive strength of 1.0 MPa or less. By using such a base material for the base material layer 1(a), a laminate having good protective performance for the contents can be obtained.

[0050] The base layer 1(a) and the base layer 2(d) may be subjected to printing or various coatings.

[0051] 4.Laminate The laminate of the present invention has at least four layers: a substrate layer 1 (a), a resin layer (b), an adhesive layer (c), and a substrate layer 2 (d), in which the substrate layer 1 (a), the resin layer (b), the adhesive layer (c), and the substrate layer 2 (d) are laminated adjacent to each other. As long as the laminate of the present invention has the above-mentioned configuration, it may have further layers. For example, a different resin layer and / or a different substrate layer may be present on the outside of substrate layer 1 (a) and / or substrate layer 2 (d). Here, examples of the different resin layers include polyethylene resins such as LDPE, C4-LLDPE, HAO-LLDPE, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-acrylic acid ester copolymer (EEA, EMA, EMMA, etc.), high density polyethylene (HDPE), and other adhesive resins such as ethylene-maleic anhydride copolymer, polypropylene resins, polystyrene resins, and other thermoplastic resins. Examples of different substrate layers include single-layer films or sheets of polyamide, polyester, polypropylene, polyethylene, ethylene-vinyl alcohol copolymer, polyvinylidene chloride, polycarbonate, etc., laminated films or sheets made of the same or different materials, stretched products of the above films or sheets, paper such as kraft paper, metal foils or metal plates such as aluminum, iron, copper, and alloys containing these as main components, plastic films or sheets vapor-deposited with metals, inorganic materials, or organic materials, cellophane, woven fabric, nonwoven fabric, paper or plastic film with a barrier coating, etc.

[0052] The method for producing the laminate is not particularly limited, but for example, the so-called extrusion coating method in which a polyethylene resin composition is melt-extruded and laminated on a substrate layer is preferred. The extrusion coating is preferably performed by laminating one or more layers by a method such as a single layer, sandwich lamination, coextrusion lamination, or tandem lamination. According to the present invention, high-speed molding is possible because of good adhesion to the substrate.

[0053] The method for ensuring the adhesion between the base layer 1(a) and the resin layer (b) is not particularly limited, but for example, the surface of the base layer 1(a) may be subjected to a surface treatment, and if necessary, an anchor coat treatment may be performed. Examples of the surface treatment method include various treatment methods such as corona discharge treatment, ozone treatment, flame treatment, and low-temperature plasma treatment. Another method is spraying ozone onto molten resin.

[0054] One embodiment of the method for producing a laminate of the present invention is a method for producing a laminate having at least four layers, namely, base material layer 1 (a), resin layer (b), adhesive layer (c), and base material layer 2 (d), by using an extrusion lamination machine, feeding base material layer 2 (d) from a feeding machine, extruding polyethylene resin composition (B) to form resin layer (b) to a predetermined thickness, feeding base material layer 1 (a) from the sand side, forming adhesive layer (c) on the surface of base material layer 2 (d) on the resin layer (b) side, and performing extrusion sand lamination processing. Here, the polyethylene resin composition (B) contains an ethylene copolymer (A) and a polyethylene resin (C).

[0055] The laminate of the present invention contains a resin layer (ii) containing a polyethylene resin composition (B) and an adhesive layer (iii) containing a specific compound, and is a laminate that has excellent adhesive strength with substrates, etc., and also has good handling properties such as easy tearing properties, and is excellent in both content protection performance and easy opening and handling properties.

[0056] The laminate of the present invention has excellent adhesive strength to substrates and the like, and also has excellent tearability, and therefore can be particularly suitably used as films for easily tearable packaging bags, films for packaging food, paper containers for liquids, packaging containers for frozen desserts such as yokan and jelly, dried foods, oils and fats, confectioneries, etc., paper bundling, paper cups, paper trays, etc. EXAMPLES

[0057] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. The measurement methods, resins, and adhesives used in the examples and comparative examples are as follows.

[0058] 1. Evaluation method for resin properties (1) Melt flow rate (MFR) The MFR of the ethylene copolymer, the polyethylene resin and the polyethylene resin composition was measured in accordance with JIS-K6922-2:1997 Appendix (190° C., 21.18 N load). (2) Density The densities of the ethylene copolymer, the polyethylene resin and the polyethylene resin composition were measured in accordance with JIS-K6922-2:1997 Appendix (23° C., in the case of low-density polyethylene).

[0059] (3) Total heat of fusion ΔHm, crystallization temperature Tc The total heat of fusion ΔHm and the crystallization temperature Tc of the ethylene copolymer were measured according to the method of JIS K7121-1987. The pellets were hot-pressed into a sheet and punched out to use as a measurement sample. The procedure was a first heating, a temperature drop, and a second heating under the following conditions. The temperature of the maximum peak height during the temperature drop was taken as Tc, and the heat of fusion in the melting curve during the second heating was taken as ΔHm. Equipment: SII NanoTechnology Inc. DSC7020 <Temperature rise and fall conditions> First temperature rise: 30℃ to 200℃ at 10℃ / min -Temperature drop: 200℃ to -30℃ at 10℃ / min Second temperature rise: -30℃ to 200℃ at 10℃ / min Temperature retention time: 5 minutes after first temperature rise, 5 minutes after temperature fall Sample size: 5mg Temperature Calibration: Indium Reference: Aluminum

[0060] (4) Amount of comonomer, number of branches and number of double bonds due to comonomer The amount of comonomer and the number of branches due to the comonomer (Y) are 13 By C-NMR, the number of double bonds (vinyl, vinylidene) is 1Measurements were performed by 1 H-NMR under the following conditions, and the number was calculated per 1,000 carbon atoms in total in the main chain and side chains. Equipment: Bruker Biospin AVANCE III cryo-400MHz Solvent: o-dichlorobenzene / bromobenzene = 8 / 2 mixed solution <Sample amount> Sample 460mg / solvent 2.3ml < 13 C-NMR · 1 H decoupling, NOE available Number of scans: 256 Flip angle: 90° · Pulse interval 20 seconds · AQ (acquisition time) = 5.45s D1 (waiting time) = 14.55s < 1 H-NMR> - Number of scans: 1400 Flip angle: 1.03° AQ (acquisition time) = 1.8s D1 (waiting time) = 0.01s

[0061] (4) Adhesive strength The obtained laminate was cut into strips 15 mm wide in the machine direction, and the interface between the base layer 1 (a) and the resin layer (b) was peeled off, and the adhesive strength was determined as the peel strength in a T-peel test with 5 specimens and a peel speed of 300 mm / min. If the resin layer (b) broke while being pulled against the base layer 1 (a) and peeled off, the adhesive strength was determined as the numerical value at the highest point on the chart.

[0062] (5) Tearability The laminates obtained were subjected to a sensory evaluation of tearability when torn by hand from the notch in both the machine direction (MD) and the direction perpendicular to the machine direction (TD). Samples that did not stretch and tore without resistance were marked with "○", and samples that stretched and encountered resistance were marked with "×".

[0063] 2.Material (1) Ethylene-based copolymer (A) The ethylene copolymers used as component (A) were (PE-1) to (PE-3) obtained by the following manufacturing method and (PE-4), a commercially available metallocene-based ethylene-α-olefin copolymer. Their physical properties are shown in Table 1.

[0064] <Method of producing (PE-1) to (PE-3)> (i) Preparation of the catalyst A catalyst solution was prepared by adding an equimolar amount of “N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate” to 0.05 moles of the complex “rac-dimethylsilylenebisindenylhafnium dimethyl” prepared by the method described in JP-A-10-218921, and diluting the mixture to 50 L with toluene.

[0065] (ii) Polymerization method A stirring autoclave type continuous reactor with an internal volume of 5.0 liters was used, the pressure inside the reactor was kept at 80 MPa, and the raw material gas was continuously supplied at a rate of 40 kg / hour while appropriately adjusting ethylene, propylene, and 1-hexene. In addition, the catalyst solution described in the above section "(i) Adjustment of catalyst" was continuously supplied, and the polymerization temperature was appropriately adjusted within the range of 150 to 250°C to obtain an ethylene copolymer. The physical properties of the obtained ethylene copolymer are shown in Table 1.

[0066] (2) Polyethylene resin (C) Polyethylene resins (PE-5) to (PE-6) having the physical properties shown in Table 1 were used.

[0067] (3) Adhesive layer (c) As the adhesive layer (iii), the following (AC-1) to (AC-3) were used. (AC-1) A mixture of Mitsui Chemicals' Takelac A-3210, Mitsui Chemicals' Takenate A-3075, and ethyl acetate in a ratio of 3:1:28 (solid content concentration: 7 wt%, containing reaction products of polyol compounds and polyisocyanate compounds) (AC-2) Seikadyne 2710A, Seikadyne 2810C(T), and ethyl acetate, manufactured by Dainichi Seika Chemicals Co., Ltd., mixed in a ratio of 1:2:15.6 (solid content concentration: 7 wt%, containing reaction products of polyol compounds and polyisocyanate compounds) (AC-3) Toyo Morton Olivine EL420, mixed with methanol in a ratio of 1:9 (does not contain reaction products of polyol compounds and polyisocyanate compounds)

[0068] (4) Base layer 1 (a) An aluminum foil (thickness: 7 μm) manufactured by Toyo Aluminum Co., Ltd. was used. Hereinafter, this is referred to as (Group-1).

[0069] (5) Base layer 2 (D) Toyobo's Espet Film T4102 (thickness: 12 μm) was used. Hereinafter, this is referred to as (Group-2).

[0070] Example 1 5% by weight of the ethylene copolymer (A) (PE-1) and 95% by weight of the polyethylene resin (C) (PE-5) were blended together and thoroughly mixed, followed by using a 40 mmφ single-screw extruder to obtain pellets of the polyethylene resin composition (B). Using an extrusion lamination molding machine, a 500 mm wide (base-2) was fed from the feeder as the base layer 2 (d), and the pellets obtained above were adjusted to a take-up speed of 100 m / min and a coating thickness of 15 μm. The (base-1) was fed from the sand side as the base layer 1 (a), and extrusion sand lamination was performed. At this time, anchor coating was performed on the base layer 2 (d) surface on the resin layer (b) side using (AC-1) as the adhesive layer (c). Next, anchor coating was performed on the opposite surface of the resin layer (b) side of the base layer 1 (a) using (AC-1), and extrusion lamination was performed with LDPE (Novatec LC600A manufactured by Japan Polyethylene Co., Ltd.) at a take-up speed of 100 m / min and a coating thickness of 20 μm, to obtain a laminate of the base layer 2 (d), adhesive layer (c), resin layer (b), base layer 1 (a), and LC600A layer. The extrusion lamination molding machine was set so that the temperature of the resin extruded from the T-die attached to the extruder with a diameter of 90 mm was 320°C, and the extrusion rate was adjusted so that the coating thickness would be the specified value when the cooling roll surface temperature was 20°C, the die width was 560 mm, and the take-up speed was 100 m / min. Next, the adhesive strength and tear resistance were evaluated using the obtained laminate. The evaluation results are shown in Table 1.

[0071] Example 2 A laminate was produced in the same manner as in Example 1, except that 10% by weight of the ethylene copolymer (A) (PE-1) and 90% by weight of the polyethylene resin (C) (PE-5) were used in Example 1. The evaluation results are shown in Table 1.

[0072] Example 3 A laminate was produced in the same manner as in Example 1, except that 20% by weight of the ethylene copolymer (A) (PE-1) and 80% by weight of the polyethylene resin (C) (PE-5) were used in Example 1. The evaluation results are shown in Table 1.

[0073] Example 4 A laminate was produced in the same manner as in Example 3, except that (PE-2) was used instead of (PE-1) which is the ethylene copolymer (A) in Example 3. The evaluation results are shown in Table 1.

[0074] Example 5 A laminate was produced in the same manner as in Example 3, except that (PE-3) was used instead of (PE-1) which is the ethylene copolymer (A) in Example 3. The evaluation results are shown in Table 1.

[0075] Example 6 A laminate was produced in the same manner as in Example 3, except that (PE-6) was used instead of (PE-5) as the polyethylene resin (C) and (AC-2) was used instead of (AC-1) as the adhesive layer (C). The evaluation results are shown in Table 1.

[0076] Comparative Example 1 A laminate was produced in the same manner as in Example 4, except that 70% by weight of the ethylene copolymer (A) (PE-2) and 30% by weight of the polyethylene resin (C) (PE-5) were used, and (AC-3) was used instead of (AC-1) as the adhesive layer (c). The evaluation results are shown in Table 1.

[0077] Comparative Example 2 A laminate was produced in the same manner as in Example 4, except that the polyethylene resin (C) (PE-6) was used instead of (PE-5) and the adhesive layer (C) (AC-3) was used instead of (AC-1). The evaluation results are shown in Table 1.

[0078] Comparative Example 3 A laminate was produced in the same manner as in Example 4, except that in Example 6, (AC-3) was used instead of (AC-1) which was the adhesive layer (iii). The evaluation results are shown in Table 1.

[0079] Comparative Example 4 A laminate was produced in the same manner as in Example 3, except that in Example 6, (PE-4) was used instead of (PE-2) of the ethylene copolymer (A) and (AC-3) was used instead of (AC-1) of the adhesive layer (C). The evaluation results are shown in Table 1.

[0080] Comparative Example 5 A laminate was produced in the same manner as in Example 1, except that the ethylene copolymer (A) was not used and a polyethylene resin composition (B) consisting of only the polyethylene resin (C) (PE-5) was used. The evaluation results are shown in Table 1.

[0081] [Table 1]

[0082] As is clear from the results in Table 1, the laminates according to the examples of the present invention are laminates that are excellent in tearability and adhesive strength to the substrate. On the other hand, in the case of the laminate having the adhesive layer (c) not containing the reaction product of the polyol compound and the polyisocyanate compound (Comparative Examples 1 to 4), the adhesive strength was small, and in particular, in Comparative Example 4, the total amount of heat of fusion, the crystallization temperature were high, and the number of branches and the number of double bonds were small, so that the tearability was also poor. When only the polyethylene resin (C) was used (Comparative Example 5), good adhesive strength was not obtained. [Industrial Applicability]

[0083] The laminate of the present invention can be used as a film for easily tearable packaging bags, a film for packaging food, a paper container for liquids, a packaging container for frozen desserts such as yokan and jelly, dried foods, oils and fats, confectionery, etc., a paper bundle, a paper cup, a paper tray, etc.

Claims

1. The laminate has at least four layers: a base layer 1 (a), a resin layer (b), an adhesive layer (c), and a base layer 2 (d), A laminate comprising a base layer 1 (a), a resin layer (b), an adhesive layer (c), and a base layer 2 (d) laminated adjacent to each other, wherein the resin layer (b) and the adhesive layer (c) each satisfy the following properties: Resin layer (ii): Contains a polyethylene resin composition (B) containing an ethylene copolymer (A) having the following characteristics (a-1) to (a-4). (a-1) MFR (190°C, 21.18N load) of 0.1 to 100g / 10min (a-2) In DSC, the total heat of fusion ΔHm is 30 to 120 J / g (a-3) Crystallization temperature Tc is 25 to 90° C. (a-4) Contains 70 to 98 mol % of structural units derived from ethylene as a major component, and 2 to 30 mol % of structural units other than ethylene as essential minor components. Adhesive layer (c): Contains a reaction product of a polyol compound and a polyisocyanate compound.

2. The laminate according to claim 1, wherein the polyethylene resin composition (B) contains a polyethylene resin (C) having the following characteristics (c-1) to (c-2): (c-1) MFR (190°C, 21.18N load) of 0.1 to 100g / 10min (c-2) density is 0.91 to 0.97 g / cm 3

3. The laminate according to claim 2, characterized in that a content ratio (weight ratio A:C) of the ethylene-based copolymer (A) to the polyethylene resin (C) in the polyethylene resin composition (B) is 98-2:2-98.

4. The laminate according to any one of claims 1 to 3, wherein the polyethylene resin composition (B) further satisfies the following properties (b-1) to (b-2). (b-1) MFR (190°C, 21.18N load) is 1 to 100g / 10min (b-2) Density is 0.88 to 0.94 g / cm 3

5. The laminate according to any one of claims 1 to 4, wherein the ethylene-based copolymer (A) further satisfies the following properties (a-5) to (a-7). (a-5) Contains 80 to 98 mol % of structural units derived from ethylene as a main component, 2 to 20 mol % of structural units derived from propylene as an essential minor component, and may contain 5 mol % or less of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the structural units derived from the third α-olefin are contained, the total amount of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (a-6) Density is 0.88 to 0.94 g / cm 3 (a-7) The total amount of vinyl and vinylidene in the ethylene copolymer is 0.35 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene groups is the number per 1,000 carbon atoms in total in the main chain and side chains as measured by NMR.)

6. The laminate according to any one of claims 1 to 5, characterized in that the ethylene-based copolymer (A) further satisfies the following characteristic (a-8). (a-8) The number of branches (Y) due to comonomers in the ethylene copolymer and the density (X) satisfy the relationship of the following formula (1). Formula (1): (Y)≧−1157×(X)+1080 (where Y is the number per 1000 total carbon atoms in the main chain and side chains as measured by NMR.)

7. The laminate according to any one of claims 1 to 6, characterized in that the ethylene-based copolymer (A) further satisfies the following characteristic (a-9): (a-9) The number of branches (Y) and density (X) due to comonomers in the ethylene copolymer satisfy the relationship of the following formula (2). Formula (2): (Y)≧−1157×(X)+1084 (where Y is the number per 1000 total carbon atoms in the main chain and side chains as measured by NMR.)

8. The oxygen permeability of the substrate layer 1 (a) is 1300 mL / m at 20° C. and 65% RH. 2 The laminate according to any one of claims 1 to 7, characterized in that the compressive strength is equal to or less than .·day·MPa.

9. The laminate according to any one of claims 1 to 8, wherein the laminate is formed by an extrusion coating method.

10. A method for producing the laminate according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Packaging material with good tearing property

    JP1998024539A

  • Packaging material having high-speed heat-sealing properties

    JP1998315409A

  • Ethylene-based polymer composition for easily tearing film and the same film

    JP2000212339A

  • Laminate, method for manufacturing the same and container using laminate

    JP2001191452A

  • Film for heat-fused printed laminate

    JP2004009566A